Combined action observation and motor imagery influences hand movement amplitude in Parkinson's disease. (April 2019) - Bek, Judith; Gowen, Emma; Vogt, Stefan; Crawford, Trevor J.; Poliakoff, Ellen
Abstract: Background: Action observation (AO) activates the motor system, influencing movement and increasing learning, and has been shown to improve speed and timing of movement in people with Parkinson's disease (PD). Importantly, however, effects on movement amplitude have not been quantitatively demonstrated. Additionally, motor imagery (MI) can increase behavioural and neural effects of AO, but the combined effects of AO+MI have not previously been explored in PD. The aim of this study was to investigate imitation of hand movement amplitude in people with PD, following (i) AO and (ii) combined AO+MI of movement trajectories. Methods: Twenty-four participants with mild to moderate PD and 24 healthy older adults observed and imitated videos showing a human hand moving between horizontal positions. Kinematics were recorded and modulation of vertical amplitude when replicating elevated vs. direct movements provided an index of imitation. After an initial set of AO trials, participants were instructed to engage in MI during observation for the remaining trials (AO+MI), emphasizing kinaesthetic (sensory) imagery. Results: Movement amplitude was imitated (modulated) for elevated vs. direct stimuli by both groups, and this imitation increased following MI instructions. Conclusions: These results demonstrate quantitatively for the first time that people with PD are able to modulate the amplitude of their hand movements following action observation, and that combining AO and MI increases imitation in PD. The effects parallel findings in healthy young participants, and indicate that combined action observation and motor imagery could be a promising therapeutic approach for PD. Highlights: Action observation influences hand movement amplitude in Parkinson's disease. Motor imagery increases the effects of action observation in people with Parkinson's disease. People with Parkinson's disease may benefit from interventions that combine action observation with motor imagery.